Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/en14196044
|View full text |Cite
|
Sign up to set email alerts
|

Design and Modelling of 3D Bionic Cathode Flow Field for Proton Exchange Membrane Fuel Cell

Abstract: Proton exchange membrane fuel cells (PEMFCs) have been utilized as a promising power source for new energy vehicles. Their performances are greatly affected by the structural design of the flow field in the bipolar plate. In this paper, we present a novel three-dimensional (3D) bionic cathode flow field, inspired by the small intestinal villi. The structural design and working principle of the 3D bionic flow field units are first described. A 3D numerical model is developed to study the mass transfer and distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…Of course, true 3-D models are needed to model multicomponent mass transfer comprehensively in the flow plates (Figure d), as 1-D + 2-D models cannot capture relevant transport phenomena such as under-the-land flow common in interdigitated and serpentine flow channels. ,, However, these models are generally too computationally intensive to bridge with device-scale models for electrochemical synthesis without sacrificing significant physics. Laminar flow is often assumed for gas transport within the flow field, but for low kinematic viscosity of gases this assumption can break down and turbulent flow may need to be considered. 3-D models also need to be selected carefully to model flow in the channels and within the porous adjacent domains.…”
Section: Survey Of Macroscale Models Employed For Modeling Porous Ele...mentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, true 3-D models are needed to model multicomponent mass transfer comprehensively in the flow plates (Figure d), as 1-D + 2-D models cannot capture relevant transport phenomena such as under-the-land flow common in interdigitated and serpentine flow channels. ,, However, these models are generally too computationally intensive to bridge with device-scale models for electrochemical synthesis without sacrificing significant physics. Laminar flow is often assumed for gas transport within the flow field, but for low kinematic viscosity of gases this assumption can break down and turbulent flow may need to be considered. 3-D models also need to be selected carefully to model flow in the channels and within the porous adjacent domains.…”
Section: Survey Of Macroscale Models Employed For Modeling Porous Ele...mentioning
confidence: 99%
“…340,342,343 However, these models are generally too computationally intensive to bridge with device-scale models for electrochemical synthesis without sacrificing significant physics. Laminar flow is often assumed for gas transport within the flow field, 344 but for low kinematic viscosity of gases this assumption can break down and turbulent flow may need to be considered. 3-D models also need to be selected carefully to model flow in the channels and within the porous adjacent domains.…”
Section: Modeling Of Flow Platesmentioning
confidence: 99%
“…Although recent studies have shifted toward research on biomimetic [51][52][53][54][55][56][57], novel geometric designs [58][59][60][61], and 3D designs [62][63][64][65][66], both conventional and modified serpentine still showed dominance as the best design through uniform fluid dynamics, greater contact surface area, and efficient liquid water drainage [67][68][69][70]. Despite the high electrochemical performance, serpentine flow fields are notorious for its high pressure drop that promotes greater parasitic power [71].…”
Section: Figurementioning
confidence: 99%
“…Reactivity of the fuel cell is based on the ability of hydrogen to diffuse towards the membrane; thus, this implies that increasing the contact area between the channel and the GDL will improve performance [15,17,18]. Another parameter that seems to have an influence on the fuel cell performance is velocity, or in other words, the generation of turbulence to improve diffusivity [6,16,17].…”
Section: Analyzed Casesmentioning
confidence: 99%
“…Inspired by small intestinal villi, Xuan et al [18] introduced a novel three-dimensional (3D) bionic cathode flow field for Proton Exchange Membrane Fuel Cells (PEMFCs). Simulation results showed that the proposed 3D bionic flow field significantly improved gas supply and water removal in the cathode, enhanced gas mass transfer by increasing contact areas with the gas diffusion layer, and lead to a more uniform distribution of currents in the membrane.…”
Section: Introductionmentioning
confidence: 99%